IMPLEMENTATION OF LOCAL TAX SERVICE POLICIES AT THE REGIONAL TAX AND RETRIBUTION MANAGEMENT AGENCY OFFICE OF PALANGKA RAYA CITY - T Kristiana; RI Poetri (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2019)
Law Number 28 of 2009 concerning Regional Taxes and Regional Levies, is the basis for implementing tax collection. The authority to impose local taxes and levies collected from the public is used to pay for services provided to the community. The potential for collecting local taxes and levies as one of the components of regional original revenue (PAD) revenue. PAD is regional revenue originating from resources within the region itself, used to finance development. Therefore, the role of local taxes and levies as one of the elements of regional original income must be optimized in their collection according to the prevailing laws and regulations.The Regional Tax and Retribution Management Agency Office of Palangka Raya City is one of the agencies that manage local taxes. Basically, the tendency of the regions to create various levies that are not in accordance with the provisions of laws and regulations and that are against the public interest can be overcome by the government by supervising each regional regulation that regulates such taxes and levies. Based on the foregoing, this study aims to describe the quality of tax services at the Regional Tax and Retribution Management Agency Office of Palangka Raya City and to describe the tax service process in increasing the realization of the target achievement of Regional Taxes and Levies at the Regional Tax and Retribution Management Agency Office of Palangka Raya City.The research method used in this research is an exploratory research method with an inductive approach. The author goes to the field to look for facts where the object to be studied is located. Researchers describe the problems that occur in the field in general, accompanied by facts and data so that the description of the existing problems becomes valid and deserves a solution. Data collection methods with in-depth interviews, observation, and documentation study. Research informants are all office employees regional Tax and Retribution Management Agency for Palangka Raya City and some tax and retribution payers in Palangkaraya City. Data analysis was performed by data reduction, data presentation, and concluding.The results of research by the Regional Tax and Retribution Management Agency (BPPRD) of Palangka Raya city were formed in 2016 based on Regional Regulation (Perda) No. 11 of 2016, the Palangka Raya City BPRD Office according to the provisions manages 9 types of local taxes consisting of Hotel Tax, Restaurant Tax, Entertainment Tax, Parking Tax, Groundwater Tax, Swallow's Nest Tax, Non-Metal Mineral, and Rock Tax, Taxes Rural and Urban Land and Buildings, Fees for Land and Buildings. In providing services to taxpayers, the Office of the Regional Tax and Retribution Management Agency for the City of Palangka Raya implements tangible service standards, reliability, responsiveness, assurance, empathy. Achievement of targets and realization averaged over 80% of the provisions for Regional Taxes and Charges.